Urgente (2016), a group theater (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
In this interview, the actors Cláudio Dias, Marcelo Sousa e Silva and Zé Walter Albinati, from Cia. Luna Lunera (BH), commented on the creation process of the piece Urgente (2016), written by the company in co-authorship with Areas Coletivo de Arte (RJ). The artists approached the creative procedures of the show's dramaturgy and staging; public reception in presentations and open rehearsals; and the presence of the band Constantina (BH) in the process of creating the piece. The interview was held at the headquarters of the interviewed group in January 2023.
Keywords: brazilian theater; dramaturgy; collaborative dynamics; procedurality